Causes and Consequences of microRNA Dysregulation - Iorio, Marilena V. (2012)
It is currently well recognized that microRNA deregulation is an hallmark of human cancer, and how an aberrant expression of these tiny regulatory RNA molecules in several cell types is not just a random association, but it plays a causal role in different steps of the tumorigenic process, from the initiation and development to progression toward the acquisition of a metastatic phenotype. Different regulatory mechanisms can control microRNA expression at a genetic or epigenetic level as well as involving the biogenesis machinery or the recruitment of specific transcription factors. The tumorigenic process implies a substantial alteration of these mechanisms, thus disrupting the equilibrium within the cell and leading to a global change in microRNA expression, with loss of oncosuppressor microRNAs and overexpression of oncomiRNAs. Here we review the main mechanisms regulating microRNAs, and the consequences of their aberrant expression in cancer, with a glance at the possible implications at a clinical point of view.